Reevaluating Ali Gomaa’s Fatwa on Bank Interest: A Detailed Ushul Fiqh Analysis - Maksalmina (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
This paper aims to reexamine Ali Gomaa’s ijtihad metodology regarding bank interest and his paradigm of thinking. Bank interest is declared usury by the majority of clerics because it is considered additional within. According to Ali Gomaa, the addition to bank interest is not considered as usury, because it is a profit from customer investments managed by the bank. This study uses qualitative method with a descriptive approach. The result of this study indicate that Gomaa’s ijtihad methodology on the fatwa of bank interest is a combination of several methods, namely bayani (studying verses and hadiths related to bank interest) then studying and selecting the opinions of previous scholars who permitted bank interest (intiqa’i) and determining the halalness of bank interest by considering the principle of jalb al-mashlahah (istishlahi). The al-maslahah is understood from Gomaa’s paradigm that the nature of a bank as an intermediary institution that functions to invest money where the capital owner (customer) also receives the results of the profit and the bank is a financial institution that can control the community in it.